Effects of technological change on non-renewable resource extraction and exploration - Eiji Sawada; Shunsuke Managi (Journal of Economic Structures, 2014)
This paper provides a non-renewable resource extraction model with both technological change and resource exploration. Especially, we consider two types of technology, extraction technology and exploration technology. We show how these technologies affect efficient non-renewable resource extraction differently. Then, progress in extraction technology drops marginal revenue of extraction and resource price by changing the structure of those dynamics, while progress in exploration technology drops marginal revenue of extraction and resource price remaining the structure of those dynamics. Finally, we illustrate the difference becomes significant when innovative technologies are developed using numerical examples.
Keywords: 330; Erschöpfbare Ressourcen; Exploration; Technischer Fortschritt; Rohstoffpreis; Theorie